Buprenorphine and postpartum contraception utilization among people with opioid use disorder: a multi-state analysis - Kevin Y. Xu; Jennifer K. Bello; Joanna Buss; Hendrée E. Jones; Laura J. Bierut; Dustin Stwalley; Hannah S. Szlyk; Caitlin E. Martin; Jeannie C. Kelly; Ebony B. Carter; Elizabeth E. Krans; Richard A. Grucza (Addiction Science & Clinical Practice)
Abstract Background The postpartum period provides an opportunity for birthing people with opioid use disorder (OUD) to consider their future reproductive health goals. However, the relationship between the use of medication for opioid use disorder (MOUD) and contraception utilization is not well understood. We used multistate administrative claims data to compare contraception utilization rates among postpartum people with OUD initiating buprenorphine (BUP) versus no medication (psychosocial services receipt without MOUD (PSY)) in the United States (US). Methods In this retrospective cohort study, we analyzed data from the Merative™ MarketScan® Multi-State Medicaid Databases 2016–2021 among postpartum women with OUD who did and did not initiate BUP during pregnancy. Our primary outcome was the receipt of prescribed highly-effective or effective contraception by 90 days postpartum. Highly-effective contraception was defined as female sterilization and long-acting reversible contraception [LARC]). Effective contraception was defined as oral contraceptive pills [OCPs], the contraceptive patch, ring, or injection. We used multivariable Poisson regression models, adjusting for sociodemographic and clinical characteristics, to measure the association of BUP (vs. PSY) on postpartum contraception utilization. Results Our sample consisted of 11,118 postpartum people with OUD. Among those, 3,443 initiated BUP and 7,675 received PSY. By 90 days postpartum, 22.4% (n = 2,487) of the cohort were prescribed contraception (21.5% PSY vs. 24.3% BUP). Among these participants, most received LARC (41.0%), followed by female sterilization (27.3%), the contraceptive injection (17.3%), pills (8.6%), ring (4.7%), and patch (1.0%), Compared to people engaged in PSY, BUP receipt was associated with a greater use of prescribed contraceptive use by 90 days postpartum (adjusted relative risk [aRR] = 1.17[1.07–1.28]), including a modestly greater use of the patch, ring, and pills, (aRR = 1.13[1.08–1.18]), but a modestly lesser use of injection contraception (aRR = 0.95[0.91–0.99]). There was no relationship observed between BUP and LARC use (aRR = 1.00[0.95–1.04]) and female sterilization (aRR = 1.01[0.98–1.06]). Conclusions Only 22% of pregnant people with OUD in our cohort used effective or highly-effective postpartum contraception. BUP receipt during pregnancy, relative to PSY, was associated with modestly greater use of prescribed effective contraceptive methods but was not associated with greater use of provider-administered contraceptive methods, such as the contraceptive injection, LARC and female sterilization.